INGLIZ VA XITOY TILLARINING MORFOSINTAKTIK VA PRAGMATIK XUSUSIYATLARI: CHOG‘ISHTIRMA TADQIQOT - Khursanova Farida Farkhod kizi (TADQIQOTLAR, 2025)
Abstract: This article presents a comparative investigation of English and Chinese morphosyntax and pragmatics. The study analyzes the structural nature of both languages, focusing on word formation, syntactic patterns, politeness strategies, discourse organization, and the role of context in meaning construction. The results indicate that English demonstrates a hybrid analytic–synthetic structure, while Chinese is strongly isolating and heavily context-driven. These differences significantly influence translation accuracy, second-language acquisition, and intercultural communication practices.